Effect of Various Growing Media and Fertilizer Levels on Growth of Antherura rubra Lour. - Fitri Kurniawati; Miranti Ariyani (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2016)
Antherura rubra Lour. is one of the critical plant at Cibodas Botanical Garden. Study  of cultivation through vegetative propagation of A. Rubra is rare. Therefore, the research of A. rubra on various of media and inorganic fertilizers is required  to conserve  A.rubra at Cibodas Botanical Garden. This study was conducted at the Nursery - Cibodas Botanic Garden for 10 months. The experiment was conducted in randomized block design (RBD) with four replications. Treatments consisted of three combinations of natural compost media with three levels of inorganic fertilizer (0, 1, and 2 dose of level), three katalek compost combination with three levels of inorganic fertilizer and a control (top soil without inorganic fertilizers). Variable tested consists of plant height, number of leaves, and dry weight shoot and root as an indicator of growth A. rubra Lour. The results showed that the growth of seedlings A. rubra Lour. on katalek compost  media's with one dose of levels inorganic fertilizer growth better than other treatments.